Теоретико-методологические основы эффективной организации заочно-дистанционного обучения в ВУЗЕ - Ризун, Н. О.; Тараненко, Ю. К. (НТУ "ХПИ", 2011)
Предложена концепция применения инновационного подхода к повышению эффективности организации заочно-дистанционного обучения путем совершенствования теории и методологии комплексного использования специализированных информационных технологий и новейших средств и техник обучения и компьютерного тестового контроля.

The concept of use of the innovative approach to improving the effectiveness of part-time and distance learning organization by means of improving of the theory and the methodology of integrated use of specialized information technologies and modern tools and techniques of learning and computer test control.
Theoretical and methodological foundations оf the effective organization of the correspondence-distance learning in high school
Keywords: инновационный подход; информационные технологии; техника обучения; тестовый контроль; innovative approach; correspondence-distance learning; information technology; techniques of learning; test control